Analysis of Factors Affecting The Interest of Individual Taxpayers in Usingdirection Management Deli River And Protected City Forest of Medan City - Martina Sukri (Golden Ratio of Taxation Studies, 2022)
Advances in information technology are now growing rapidly in all aspects of people's lives. Advances in information technology bring convenience to information processing. The distribution of information that can be spread freely and quickly using information technology makes globalization unstoppable